2017
DOI: 10.1093/rheumatology/kew464
|View full text |Cite|
|
Sign up to set email alerts
|

Dosing down with biologic therapies: a systematic review and clinicians’ perspective

Abstract: The effectiveness of biologic therapies now means that remission or low disease activity are realistic targets for treatment. However, after achieving remission/low disease activity, the next steps remain unclear. The aim of this publication was to conduct a broad systematic literature review to evaluate dosing down of biologics. After screening papers and abstracts for relevance and application of inclusion/exclusion criteria, a structured extraction process was used to collect information on the included stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 52 publications
1
42
0
3
Order By: Relevance
“…In PsA, a systematic review summarised the limited current evidence on dose optimisation and withdrawal of biological disease-modifying anti-rheunatic drugs (bDMARDs) in PsA, and favoured dose optimisation over discontinuation because of the substantial risk of loss of remission [14]. So far, no randomised controlled trials have been performed on dose optimisation strategies in PsA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PsA, a systematic review summarised the limited current evidence on dose optimisation and withdrawal of biological disease-modifying anti-rheunatic drugs (bDMARDs) in PsA, and favoured dose optimisation over discontinuation because of the substantial risk of loss of remission [14]. So far, no randomised controlled trials have been performed on dose optimisation strategies in PsA.…”
Section: Introductionmentioning
confidence: 99%
“…In axSpA, two systematic reviews concluded that more or less comparable to PsA, TNFi reduction strategies are successful in sustaining clinical remission or LDA in about 50% of patients but that discontinuation often leads to flares [14,15]. A few randomised controlled trials have been conducted on dose optimisation or discontinuation in axSpA, where similar results were shown as in RA with regard to maintaining remission by fixed dose reduction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Infliximab (IFX), an inhibitor of TNF-α, is one of the biological disease-modifying antirheumatic drugs (DMARDs); combined use of IFX and methotrexate (MTX) yields clinical and radiographic benefits in patients with RA with inadequate response to MTX (MTX-IR) 4. Because the therapeutic effects of IFX (plus MTX) have been demonstrated in several clinical studies,5–9 the goal of RA treatment has expanded from the achievement of clinical remission to sustained remission without biological DMARDs, particularly in patients with RA in sustained remission 10–15…”
Section: Introductionmentioning
confidence: 99%
“…2019;13(4):79-83 Пациент Ш., 32 лет, поражение кожи до (а) и после (б) первой инъекции СЕК Сегодня, в эпоху широкого применения ГИБП, проблема оптимизации терапии крайне актуальна, особенно у больных, достигших ремиссии. С целью снижения стоимости лечения, а также минимизации рисков нежелательных реакций при длительном применении ГИБП во всем мире изучаются вопросы модификации дозы или отмены ГИБП при достижении низкой/минимальной активности заболевания (Minimal Disease Activity, MDA) или ремиссии [17,18]. Выполнены работы [17,19], в которых оценивались частота и клинические предикторы успешной отмены ГИБП, но только у пациентов с ревматоидным артритом.…”
unclassified
“…С целью снижения стоимости лечения, а также минимизации рисков нежелательных реакций при длительном применении ГИБП во всем мире изучаются вопросы модификации дозы или отмены ГИБП при достижении низкой/минимальной активности заболевания (Minimal Disease Activity, MDA) или ремиссии [17,18]. Выполнены работы [17,19], в которых оценивались частота и клинические предикторы успешной отмены ГИБП, но только у пациентов с ревматоидным артритом. Необходимо отметить, что даже в случае достижения стойкой ремиссии (6 мес) обострение РА в течение 1 года после отмены ГИБП наблюдалось у 50% пациентов.…”
unclassified